Alteration of key hyporheic functions through biological and physical clogging along a nutrient and fine‐sediment gradient. Issue 5 (7th November 2014) - Hartwig, Melanie; Borchardt, Dietrich; Boudell, Jere A.; Dixon, Mark D.; Rood, Stewart B.; Stromberg, Juliet C.
Abstract The hyporheic zone bears key hydro‐ecological functions such as hydrological connectivity of surface and groundwater ecosystems and biogeochemical regulation of substance dynamics. These functions are controlled by the sediment permeability that in turn is affected by biological and physical clogging. A number of conceptual models have been developed on the interactions and feedbacks between these functionalities; surprisingly, comprehensive field data are scarce. Thus, the aim of this study was to assess these functions and their vulnerability along a stressor gradient of nutrient and fine‐sediment input at riffle scale. Three sampling sites along the Kharaa River (Northern Mongolia) were selected that represented conditions from being unaffected, affected by biological clogging and impaired by physical clogging. A significant impact on the hydrological connectivity was detected, as the vertical downward flux and the solute penetration depth decreased along the reaches. Simultaneously, the heterogeneity in biogeochemical patterns and the vertical extent of the oxygen gradients declined. Whilst biological clogging was apparently unstable and the biofilm supported the hyporheic organic carbon pool, it revealed to affect the two functions to a lesser extent when compared with physical clogging. In contrast, physical clogging seemed to be more permanent and restricted microbial metabolism to the uppermost centimetres, thus decreasing the active sediment depth. Moreover, fine‐sediment particles enhanced the sediment surface area, thereby creating a high respiration potential that resulted in high values of community respiration and subsequent oxygen depletion. Concluding, the control of fine‐sediment emissions has to be a priority issue in river restoration and catchment management. Copyright © 2014 John Wiley & Sons, Ltd.